ASUHAN KEPERAWATAN PADA NY. S DENGAN TB PARU DI RUANG ISOLASI RSUD BANGKINANG - IQROMIL HADI; Yenny Safitri (Jurnal Spektrum Kesehatan Indonesia, 2025)
Pulmonary tuberculosis (TB) is one of the infectious diseases that remains a major challenge in public health, caused by Mycobacterium tuberculosis and spreads through sputum droplets when the patient coughs or sneezes. Based on data from RSUD Bangkinang in 2024, the number of pulmonary TB cases remains high, particularly in the isolation ward. This study aims to describe the nursing care process provided to Mrs. S, a patient with pulmonary TB treated in the isolation room of RSUD Bangkinang. The method used is a case study approach covering assessment, nursing diagnosis, planning, implementation, and evaluation. The assessment revealed complaints such as productive cough, chest pain during coughing, and sleep disturbances due to nighttime coughing. The nursing diagnoses included ineffective airway clearance, acute pain, and disturbed sleep pattern. Interventions based on the Indonesian Nursing Intervention Standards (SIKI) were implemented, including airway management, pain management, and sleep support. Implementation was carried out over three days with periodic evaluation. The results showed improvement in the patient's condition, including reduced coughing, decreased chest pain, and better sleep quality. Based on the findings, it is expected that the patient and her family can continue independent care at home and maintain health status. Family support plays a vital role in the patient's recovery process from pulmonary TB.